Greenhouse microclimate environment adaptive control based on a wireless sensor network - Wang, Lina; Wang, Binrui (International Journal of Agricultural and Biological Engineering, 2020)
Environmental parameter measurements from various sensors spatially distributed in greenhouse crops can be used to create an accurate and detailed depiction of the climate in different regions of the greenhouse. Microclimate environments have an impact on crop yield, productivity, quantitative and qualitative characteristics of plants, and various plant diseases. In this study, an automatic monitoring system based on a wireless sensor network was designed to monitor the survival rate of greenhouse crops. The system design includes a sensor model selection and placement process, host computer monitoring software and communication module design. The Zigbee protocol was used for wireless communication between the nodes. The proposed fuzzy-PID controller was easy to design and highly adaptive to the measurement errors of the sensors. The test results show that the system valuable for monitoring the environment in the greenhouse, where it was successful in controlling and maintaining an optimal microclimate condition. Keywords: greenhouse, microclimate control, wireless sensor network, fuzzy-PID control DOI: 10.25165/j.ijabe.20201303.5027 Citation: Wang L N, Wang B R. Greenhouse microclimate environment adaptive control based on a wireless sensor network. Int J Agric & Biol Eng, 2020; 13(3): 64–69.